Controlled synthesis method of barium titanate nanowire

By using potassium hydroxide and stirred hydrothermal reaction technology, combined with acid solution treatment, the problems of length-to-diameter ratio and morphological uniformity of barium titanate nanowires in the prior art were solved, and titanium acid with high purity and uniform length-to-diameter are prepared. Barium nanowires meet the needs of high energy storage and processing performance and reduce production costs.

CN119191342APending Publication Date: 2024-12-27SHENZHEN HFC SHIELDING PRODS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411257698.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art is difficult to prepare barium titanate nanowires with high aspect ratio and uniform morphology, resulting in the product being easily broken and has many particles, making it difficult to meet the needs of high energy storage and excellent processing performance.

Method used

Potassium hydroxide is used as the alkali solution to control the potassium-titanium molar ratio between 0.2 and 0.3. By stirring the hydrothermal reaction, the replacement reaction of barium ions is regulated. Combined with two-step hydrothermal method and acid solution treatment, a relatively large diameter and diameter are prepared. Uniform barium titanate nanowires.

Benefits of technology

It has achieved the preparation of barium titanate nanowires with a length of 1 to 2 μm and a diameter of 180 to 230 nm. It has high purity and excellent morphological characteristics, meets the needs of high energy storage and processing performance, and reduces production costs, which is suitable for large-scale Large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191342A_ABST
    Figure CN119191342A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of nano materials and technologies, and particularly relates to a barium titanate nanowire and a controlled synthesis method thereof, and the method comprises the following steps: (S1) preparing a potassium hydroxide solution, adding a titanium source into the potassium hydroxide solution, and fully mixing, with the molar ratio of potassium atoms to titanium atoms being 0.2-0.3; (S2) transferring the mixed solution prepared in the step (S1) into a reaction kettle, carrying out hydrothermal reaction in a stirring state, taking out after the reaction is completed, cleaning and drying to obtain a precursor nanowire; (S3) preparing a barium source water solution, and adding the precursor nanowire into the barium source water solution according to a barium-titanium substance ratio of (1: 1.1)-(1.2: 1) until the precursor nanowire and the barium source water solution are fully mixed; (S4) transferring the mixed solution obtained in the step (S3) into a reaction kettle, carrying out hydrothermal reaction in a stirring state, cooling and taking out a product; and (S5) after treating the product with an acid solution, cleaning and drying to obtain the nanowire. The prepared barium titanate nanowire is high in length-diameter ratio, free of particles and uniform in morphology, and can be widely applied to the field of dielectric materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano materials and technology, and specifically relates to a barium titanate nanowire and a preparation method thereof. Background Art

[0002] Barium titanate (BaTiO 3 ) Due to its high dielectric constant, low dielectric loss, excellent ferroelectric and piezoelectric properties, as well as withstand voltage and insulation properties, it is widely used in electronic components such as multilayer ceramic capacitors (MLCC), thermistors (PTC), optoelectronic devices, and various random access memories. However, in recent years, with the rapid development of the electronic information industry, the requirements for electronic equipment, household appliances, and transportation equipment have become increasingly higher, and electronic components have developed towards miniaturization, intelligence, and precision. Therefore, there is a wide demand for dielectric materials with high energy storage and excellent processing performance.

[0003] Compared with existing barium titanate nanoparticles, barium titanate nanowires not only have the unidirectionality of a one-dimensional structure, but also have the advantages of high response and high piezoelectric performance. They are a very promising nanomaterial, and sensors based on barium titanate nanowire materials and polymer composites have been used in many fields. In addition, because barium titanate nanowires have a high aspect ratio, they can improve the dielectric constant of the composite material, thus meeting the requirements of high energy storage and excellent processing performance.

[0004] Currently, hydrothermal synthesis is considered to be the most promising method for synthesizing one-dimensional BaTiO 3 One of the methods for producing nanowires, it can control the ion exchange process in the precursor structure, and has high crystallinity, low cost, simple process, and potential for large-scale production. The traditional hydrothermal method is a static reaction during the hydrothermal process, which will lead to uneven mixing of the reaction solution and a large number of product particles, which is not conducive to the generation of nanowires with a specific aspect ratio; at the same time, the existing technology uses conventional sodium hydroxide, lithium hydroxide, etc. as alkaline solutions, but it is difficult to control the aspect ratio of barium titanate nanowires, and the effect of preparing barium titanate nanowires with a high aspect ratio is not ideal. The reason is that the ionic radius of sodium ions and lithium ions is small. When they are replaced with barium ions in the second step of the hydrothermal reaction, the barium ions will cause a large lattice distortion after replacing the sodium ions or lithium ions, making the BaTiO 3 Nanowires are prone to breakage, and it is difficult to obtain BaTiO with a high aspect ratio, uniform morphology, and few particles. 3 Nanowires. Summary of the invention

[0005] In view of the defects existing in the above-mentioned traditional methods for preparing barium titanate nanowires, the present invention provides a controlled synthesis method for barium titanate nanowires, which solves the technical problem that it is difficult to prepare barium titanate nanowires with a higher aspect ratio in the prior art, so as to achieve the technical effect of preparing barium titanate nanowires with a larger aspect ratio, no particles and uniform morphology.

[0006] To achieve the above object, the present invention provides the following technical solution: a controlled synthesis method of barium titanate nanowires, comprising the following steps:

[0007] S1: preparing a potassium hydroxide aqueous solution, slowly adding a titanium source into the potassium hydroxide solution until fully mixed, wherein the molar ratio of potassium atoms to titanium atoms is 0.2 to 0.3;

[0008] S2: transferring the mixed solution prepared in S1 to a reaction kettle, performing a hydrothermal reaction under stirring, taking out after the reaction is completed, washing and drying to obtain precursor nanowires;

[0009] S3: preparing a barium source aqueous solution, and slowly adding the precursor nanowires to the barium source solution according to a molar ratio of barium to titanium of 1:1.1 to 1.2:1 until fully mixed;

[0010] S4: transferring the mixed solution obtained in S3 to a reaction kettle, performing a hydrothermal reaction under stirring, and taking out the product after cooling;

[0011] S5: After the product is treated with an acid solution, it is washed to neutrality and dried to obtain nanowires.

[0012] Preferably, the titanium source is titanium dioxide or tetrabutyl titanate, and the barium source is barium hydroxide octahydrate.

[0013] Preferably, the concentration of the potassium hydroxide aqueous solution is 10-12 mol / L, and the concentration of the barium source aqueous solution is 0.05-1 mol / L.

[0014] Preferably, the hydrothermal reaction temperature in step S2 is above 200-240° C., the reaction time is 12-72 h, and the stirring rate is 500-1000 rpm.

[0015] Preferably, in step S4, the hydrothermal reaction temperature is 140-210° C., the reaction time is 1-16 h, and the stirring rate is 500-1000 rpm.

[0016] Preferably, the acid solution is acetic acid or nitric acid solution.

[0017] Preferably, the cleaning solutions in steps S2 and S5 are deionized water and ethanol; and the drying temperature is 60-80°C.

[0018] According to another aspect of the present invention, a nanowire prepared by a controlled synthesis method of barium titanate nanowires is provided, preferably having a length of 1 to 2 μm and a diameter of 180 to 230 nm.

[0019] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:

[0020] (1) The present invention uses potassium hydroxide as the alkaline solution. Since the ionic radius of potassium ions in potassium hydroxide is close to that of barium ions, the lattice distortion caused by the substitution reaction between potassium ions and barium ions in the second step of the hydrothermal reaction can be effectively reduced, thereby obtaining barium titanate nanowires with a higher aspect ratio. At the same time, the molar ratio of potassium ions to titanium ions is controlled to be 0.2-0.3. If the potassium-titanium ratio is relatively large, the prepared nanowires will be relatively dispersed and the yield will be small. If the potassium-titanium ratio is relatively small, the precursor nanowires will be mixed together and difficult to disperse, and the length of the prepared nanowires will also be short.

[0021] (2) The present invention adopts a stirring method to carry out the hydrothermal reaction, and adopts a stirring rate in the range of 500-1000rpm to fully mix the titanium source and potassium hydroxide, which greatly improves the reaction rate. At the same time, it can break the dissolution-recrystallization balance in the static hydrothermal reaction process, accelerate the directional growth of the surface of small-sized nanowires, and make the prepared nanowires anisotropic. The control of the stirring rate is to avoid that the stirring rate is too high, which will lead to more nanowire particles, and the stirring rate is too low, which will lead to insufficient reaction and uneven morphology of the prepared nanowires.

[0022] (3) The method for preparing barium titanate nanowires provided by the present invention is a two-step hydrothermal method, which has a simple process, low equipment requirements, low production cost, and is easy to promote on a large scale.

[0023] (4) The preparation method for controlling the synthesis conditions of barium titanate nanowires provided by the present invention can obtain barium titanate nanowires with high purity, a length of 1 to 2 μm, and a diameter of 180 to 230 nm by preferably controlling the molar ratio of potassium atoms in the sodium hydroxide solution to titanium atoms in the titanium source to 0.2 to 0.3, preferably controlling the amount ratio of barium titanium substances to 1:1.1 to 1.2:1, and preferably controlling the stirring rate to 500 to 1000 rpm. Mass production of the barium titanate nanowires is now possible. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the following is a brief introduction to the drawings required for the description of the specific implementation methods. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0025] Figure 1This is a SEM image of barium titanate nanowires prepared in Example 1 of the present invention;

[0026] Figure 2 XRD diagram of barium titanate nanowires provided in Example 1 of the present invention;

[0027] Figure 3 This is a Raman scattering diagram of the barium titanate nanowires provided in Example 1 of the present invention;

[0028] Figure 4 This is a SEM image of barium titanate nanowires prepared in Comparative Example 1 of the present invention;

[0029] Figure 5 This is a SEM image of barium titanate nanowires prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0031] Embodiment 1:

[0032] A method for preparing barium titanate nanowires comprises the following steps:

[0033] Step 1: Prepare 60 ml of 12M KOH solution with 100 ml of polytetrafluoroethylene liner, take 4 g of TiO 2 Add it in a stirring state and stir magnetically for 60 minutes until fully mixed.

[0034] Step 2: The mixed solution in step 1 is loaded into a reaction kettle, placed in an oven, and stirred and heated at 200°C at a stirring rate of 500 rpm for 24 hours. The obtained product is rinsed with deionized water and anhydrous ethanol until neutral, and then placed in an oven at 80°C for drying to obtain potassium tetratitanate nanowires.

[0035] Step 3: Dissolve barium titanate octahydrate in deionized water to prepare 60 ml of 0.05 M barium titanate octahydrate solution, and slowly add 0.3375 g of potassium tetratitanate nanowires washed and dried in step 2 in a 1:1 barium to titanium ratio while stirring, and stir until well mixed.

[0036] Step 4: The mixed solution in step 3 was placed in a reactor, and heated at 140° C. with stirring at a rate of 500 rpm for 10 h. The product was taken out after the reactor was cooled to room temperature.

[0037] Step 5: The product obtained in step 4 is treated with acetic acid to remove barium carbonate, then washed with deionized water and anhydrous ethanol until neutral, and then placed in an oven at 80° C. to dry to obtain barium titanate nanowires.

[0038] The scanning electron microscope spectrum of the barium titanate nanowires prepared in this specific embodiment is as follows: Figure 1 As shown, according to the results, the barium titanate nanowires prepared by the method provided by the present invention have a uniform aspect ratio and contain a small amount of barium carbonate impurities. The obtained barium titanate nanowires have a length of 1.8 μm and a diameter of 180 nm.

[0039] Figure 2 The XRD spectrum of the product shows that the absorption peaks of the barium titanate nanowires prepared by the hydrothermal synthesis method and the standard card are completely matched, among which the strongest diffraction peaks corresponding to 2θ=22.2°, 31.6°, 38.9°, 45.2°, 51.2° and 55.9° are consistent with those of BaTiO 3 The (100), (110), (111), (200), (210) and (211) crystal planes of the characteristic diffraction peaks of (JCPDS, 79-2263) completely correspond to each other. Therefore, the products with these diffraction peaks in the XRD spectrum can be identified as BaTiO 3 And according to the XRD spectrum, it can be seen that the prepared BaTiO 3 The nanowires are of high purity and contain only a small amount of impurities.

[0040] Figure 3 The Raman scattering diagram of the product shows that the peaks at 184, 250, 304, 516, and 716 cm -1 The appearance of Raman peaks proves that the prepared barium titanate nanowires have a tetragonal phase structure, which makes the nanowires ferroelectric and lays the foundation for subsequent applications in dielectric materials.

[0041] Embodiment 2:

[0042] A method for preparing barium titanate nanowires comprises the following steps:

[0043] Step 1: Prepare 60 ml of 12M KOH solution with 100 ml of polytetrafluoroethylene liner, add 1.5 ml of tetrabutyl titanate into it under stirring, and stir magnetically for 60 minutes until fully mixed.

[0044] Step 2: The mixed solution in step 1 is loaded into a reaction kettle, placed in an oven, and stirred and heated at 200°C at a stirring rate of 1000 rpm for 48 hours. The obtained product is rinsed with deionized water and anhydrous ethanol until neutral, and then placed in a 70°C oven for drying to obtain potassium tetratitanate nanowires.

[0045] Step 3: Dissolve barium titanate octahydrate in deionized water to prepare 60 ml of 0.1 M barium titanate octahydrate solution, and slowly add 0.75 g of potassium tetratitanate nanowires washed and dried in step 2 according to a barium-titanium substance ratio of 1:1.1 under stirring, and stir until mixed evenly.

[0046] Step 4: The mixed solution in step 3 was placed in a reactor, and heated at 210° C. with stirring at a rate of 1000 rpm for 1 h. The product was taken out after the reactor was cooled to room temperature.

[0047] Step 5: The product obtained in step 4 is treated with acetic acid to remove barium carbonate, then washed with deionized water and anhydrous ethanol until neutral, and then placed in an oven at 70° C. to dry to obtain barium titanate nanowires.

[0048] Embodiment 3:

[0049] A method for preparing barium titanate nanowires comprises the following steps:

[0050] Step 1: Prepare 60 ml of 12M KOH solution with 100 ml of polytetrafluoroethylene liner, add 1.5 ml of tetrabutyl titanate into it under stirring, and stir magnetically for 60 minutes until fully mixed.

[0051] Step 2: The mixed solution in step 1 is loaded into a reaction kettle, placed in an oven, and heated at 200°C with a stirring rate of 800 rpm for 24 hours. The obtained product is rinsed with deionized water and anhydrous ethanol until neutral, and then placed in a 70°C oven for drying to obtain potassium tetratitanate nanowires.

[0052] Step 3: Dissolve barium titanate octahydrate in deionized water to prepare 60 ml of 0.1 M barium titanate octahydrate solution, and slowly add 0.81 g of potassium tetratitanate nanowires washed and dried in step 2 in a stirring state according to a barium-titanium substance ratio of 1:1.2, and stir until mixed evenly.

[0053] Step 4: The mixed solution in step 3 was placed in a reactor, and heated at 160° C. with stirring at a rate of 900 rpm for 15 h. The product was taken out after the reactor was cooled to room temperature.

[0054] Step 5: The product obtained in step 4 is treated with acetic acid to remove barium carbonate, then washed with deionized water and anhydrous ethanol until neutral, and then placed in an oven at 70° C. to dry to obtain barium titanate nanowires.

[0055] Comparative Example 1

[0056] Step 1: Prepare 60 ml of 12M NaOH solution with 100 ml of polytetrafluoroethylene liner, take 4 g of TiO 2Add it in a stirring state and stir magnetically for 60 minutes until fully mixed.

[0057] Step 2: The mixed solution in step 1 is loaded into a reaction kettle, placed in an oven, and stirred and heated at 200°C at a stirring rate of 500 rpm for 24 hours. The obtained product is rinsed with deionized water and anhydrous ethanol until neutral, and then placed in an oven at 80°C for drying to obtain potassium tetratitanate nanowires.

[0058] Step 3: Dissolve barium titanate octahydrate in deionized water to prepare 60 ml of 0.05 M barium titanate octahydrate solution, and slowly add 0.3375 g of potassium tetratitanate nanowires washed and dried in step 2 in a 1:1 barium to titanium ratio while stirring, and stir until well mixed.

[0059] Step 4: The mixed solution in step 3 was placed in a reactor, and heated at 140° C. with stirring at a rate of 500 rpm for 10 h. The product was taken out after the reactor was cooled to room temperature.

[0060] Step 5: The product obtained in step 4 is treated with acetic acid to remove barium carbonate, then washed with deionized water and anhydrous ethanol until neutral, and then placed in an oven at 80° C. to dry to obtain barium titanate nanowires.

[0061] The scanning electron microscope spectrum of the barium titanate nanowires prepared in this specific embodiment is as follows: Figure 4 As shown, Figure 4 and Figure 1 By comparison, it can be seen from the results that the aspect ratio of the barium titanate nanowires prepared by the method provided by the present invention is smaller than that of the barium titanate nanowires prepared in Example 1, and contains more particles.

[0062] Comparative Example 2

[0063] Step 1: Prepare 60 ml of 12M LiOH solution with 100 ml of polytetrafluoroethylene liner, take 4 g of TiO 2 Add it in a stirring state and stir magnetically for 60 minutes until fully mixed.

[0064] Step 2: The mixed solution in step 1 is loaded into a reaction kettle, placed in an oven, and stirred and heated at 200°C at a stirring rate of 500 rpm for 24 hours. The obtained product is rinsed with deionized water and anhydrous ethanol until neutral, and then placed in an oven at 80°C for drying to obtain potassium tetratitanate nanowires.

[0065] Step 3: Dissolve barium titanate octahydrate in deionized water to prepare 60 ml of 0.05 M barium titanate octahydrate solution, and slowly add 0.3375 g of potassium tetratitanate nanowires washed and dried in step 2 in a 1:1 barium to titanium ratio while stirring, and stir until well mixed.

[0066] Step 4: The mixed solution in step 3 was placed in a reactor, and heated at 140° C. with stirring at a rate of 500 rpm for 10 h. The product was taken out after the reactor was cooled to room temperature.

[0067] Step 5: The product obtained in step 4 is treated with acetic acid to remove barium carbonate, then washed with deionized water and anhydrous ethanol until neutral, and then placed in an oven at 80° C. to dry to obtain barium titanate nanowires.

[0068] The scanning electron microscope spectrum of the barium titanate nanowires prepared in this specific embodiment is as follows: Figure 4 As shown, Figure 4 and Figure 1 By comparison, it can be seen from the results that the aspect ratio of the barium titanate nanowires prepared by the method provided by the present invention is smaller than that of the barium titanate nanowires prepared in Example 1, and contains more particles.

[0069] Comparative Example 3

[0070] Step 1: Prepare 60 ml of 12M KOH solution with 100 ml of polytetrafluoroethylene liner, take 4 g of TiO 2 Add it in a stirring state and stir magnetically for 60 minutes until fully mixed.

[0071] Step 2: The mixed solution in step 1 is loaded into a reaction kettle, placed in an oven, and heated at 200°C for 24 hours. The obtained product is rinsed with deionized water and anhydrous ethanol until neutral, and then placed in an oven at 80°C for drying to obtain potassium tetratitanate nanowires.

[0072] Step 3: Dissolve barium titanate octahydrate in deionized water to prepare 60 ml of 0.05 M barium titanate octahydrate solution, and slowly add 0.3375 g of potassium tetratitanate nanowires washed and dried in step 2 in a 1:1 barium to titanium ratio while stirring, and stir until well mixed.

[0073] Step 4: Place the mixed solution in step 3 into a reactor, heat it at 140°C for 10 hours, and take out the product after the reactor cools to room temperature.

[0074] Step 5: The product obtained in step 4 is treated with acetic acid to remove barium carbonate, then washed with deionized water and anhydrous ethanol until neutral, and then placed in an oven at 80° C. to dry to obtain barium titanate nanowires.

[0075] The scanning electron microscope spectrum of the barium titanate nanowires prepared in this specific embodiment is as follows: Figure 5 As shown, Figure 5 and Figure 1 By comparison, it can be seen from the results that the aspect ratio of the barium titanate nanowires prepared by the method provided by the present invention is smaller than that of the barium titanate nanowires prepared in Example 1, contains more particles, and the morphology of the barium titanate nanowires is uneven.

[0076] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A controlled synthesis method of barium titanate nanowires, characterized in that: The steps include: S1: adding a titanium source to a potassium hydroxide aqueous solution until fully mixed to obtain a mixed solution, wherein the molar ratio of potassium atoms to titanium atoms is 0.2 to 0.3; S2: transferring the mixed solution prepared in S1 to a reaction kettle, performing a hydrothermal reaction under stirring, taking out after the reaction is completed, and obtaining precursor nanowires after washing; S3: adding a barium source aqueous solution to the precursor nanowires obtained in S2 until fully mixed, and controlling the ratio of the amount of barium to titanium to be 1:1.1 to 1.2:1; S4: transferring the mixed solution obtained in S3 to a reaction kettle, performing a hydrothermal reaction under stirring, and taking out the product after cooling; S5: After the product is treated with an acid solution, it is washed and dried to obtain barium titanate nanowires.

2. The controlled synthesis method of barium titanate nanowires according to claim 1, characterized in that: The titanium source is titanium dioxide or tetrabutyl titanate, and the barium source is barium hydroxide octahydrate.

3. The controlled synthesis method of barium titanate nanowires according to claim 1, characterized in that: The concentration of the potassium hydroxide aqueous solution is 10-12 mol / L, and the concentration of the barium source aqueous solution is 0.05-1 mol / L.

4. The controlled synthesis method of barium titanate nanowires according to claim 1, characterized in that: In step S2, the hydrothermal reaction temperature is 200-240° C., the reaction time is 12-72 h, and the stirring rate is 500-1000 rpm.

5. The controlled synthesis method of barium titanate nanowires according to claim 1, characterized in that: In step S4, the hydrothermal reaction temperature is 140-210° C., the reaction time is 1-16 h, and the stirring rate is 500-1000 rpm.

6. The controlled synthesis method of barium titanate nanowires according to claim 1, characterized in that: The acid solution is acetic acid or nitric acid solution.

7. The controlled synthesis method of barium titanate nanowires according to claim 1, characterized in that: The cleaning in steps S2 and S5 is first performed using deionized water and then using ethanol; the drying temperature is 60-80°C.